Fauna and Larval Habitats Characteristics of Mosquitoes (Diptera: Culicidae) in Golestan Province, Northeast of Iran, 2014-2015 - Aioub Sofizadeh; Hamid Reza Shoraka; Fatemeh Mesgarian; Ghorban Mohammad Ozbaki; Abdolsamad Gharaninia; Ebrahim Sahneh; Rohollah Dankoob; Ali Malaka; Saeid Fallah; Shamsaddin Nemani (Tehran University of Medical Sciences, 2018)
Background: Mosquitoes (Diptera: Culicidae) is one of the most medically important families of Diptera. The aims of this study were to determine fauna and larval habitat characteristics of mosquitoes in Golestan Province, during 2014-15. Methods: This study was conducted in larval habitats of mosquitoes and installed ovitraps in 14 districts of Golestan Province, Northern Iran in 2015. Samples were collected with a scoop by ladle handling for entomology. The collected larvae were transferred to Laboratory of Medical Entomology in lactophenol solution. Then microscopic slides were prepared using de Faure's formula. Species of each sample was recognized using diagnostic criteria to identify the Culicidae species. Characteristics of larval breeding places were studied based on the habitat type (Permanent or temporary), water conditions (Clear or turbid, stagnant or running), vegetation (out, in, underwater vegetation or without vegetation), sunlight exposure (Full or partial sunlight) and so on. Data were analyzed using SPSS. Results: Overall, 5661 third- and fourth- instars larvae of mosquitoes were collected and 5 genera and 14 species were identified: Anopheles hyrcanus, An. maculipennis, An. pseudopictus, An. superpictus, Culex hortensis, Cx. mimiticus, Cx. perexiguus, Cx. pipiens, Cx. pusillus, Cx. theileri, Cx. tritaeniohynchus, Culiseta longiareolata, Ochlerotatus caspius, Uranotaenia unguiculata. Culex pipiens was recognized as predominant species of the family. Among the detected species, Cx. pusillus reported for the first time from Golestan Province. Conclusion: Due to the high species diversity of Culicidae, ecology of medical important species such as Cx. pipiens and Cx. tritaeniorhynchus needs more investigations.